The Effect of Annuity Insurance on Savings and Inequality - Kotlikoff, Laurence J.; Shoven, John; Spivak, Avia (Journal of Labor Economics, 1986)
This paper examines the amount of precautionary savings and wealth inequality arising from life-span uncertainty by comparing saving behavior under perfect insurance arrangements with that arising under imperfect arrangements, namely, when longevity risk can be pooled only with members of one's own family. The central findings of the paper are that (1) perfecting insurance arrangements can sharply lower savings in both intergenerationally altruistic and life-cycle economies and that (2) in altruistic economies perfecting annuity insurance can greatly influence inequality; indeed, in the long run in our model, switching from imperfect family insurance to perfect insurance can mean the difference between absolute inequality and absolute equality.